Changes in drivers' viewing frequency, maneuver duration, and degree of difficulty during back-in parking maneuver with different conditions of parking spaces. Issue 1 (November 2021) - Setiawan, R; Dammara, A S; Cahyadi, B; Widarno, B; Njoko, F H; Noviani, M
Abstract: To some people, back-in parking maneuver is a relatively hard thing to do. However, previous studies have proven that back-in parking is safer than head-in parking because when exiting the parking space (back-out) from head-in parking, the driver's field of view is more limited, thus increasing the chance of an accident. This study aims to determine the changes in the driver's viewing frequency on the rear-view mirror, maneuver duration, and degree of difficulty during back-in parking maneuvers. Data collection was obtained from 45 participants who tried to park their cars in a parking space with an angle of 30°, 45°, 60°, 90°, each with four different conditions of parking spaces. The driver's viewing frequency on each rear-view mirror (left, right and center) and maneuver duration were obtained from a dashcam and an external camera recording. The difficulty level for maneuvering was filed according to the driver's opinion during the experiment for each parking space condition. Based on the data analysis, it was proven that the existence of cars parked on either side of that parking space (obstacles), parking space line signs, and both simultaneously increase the driver's viewing frequency and maneuver duration when doing back-in parking maneuver, but at the same time, ease the parking maneuver, according to the driver.